Improved overall survival of metastatic renal cell carcinoma patients in the era of modern tyrosine kinase inhibitors and immune checkpoint inhibitors: results from a real-life, population-based Austrian study comprising three decades of follow-up. (November 2022) - Fluhrer, Hannah; Hutterer, Georg C.; Golbeck, Sylvia; Stidl, Michael; Niedrist, Tobias; Pichler, Renate; Mischinger, Johannes; Seles, Maximilian; Mannweiler, Sebastian; Spiegelberg, Jasmin; Bauernhofer, Thomas; Jost, Philipp J.; et al.
Background: The treatment landscape of metastatic renal cell carcinoma (mRCC) has substantially advanced over the last three decades, whereby data from controlled clinical trials indicate significant improvements regarding patients' overall survival (OS) in highly selected patient cohorts. The aim of this study is to evaluate the impact of potentially game changing drugs on patients' outcomes by comparing three different historical mRCC treatment eras. Methods: In all, 914 mRCC patients who were diagnosed between July 1985 and September 2020 were included into this observational study and assigned to three different treatment eras ['cytokine', 'first-generation tyrosine kinase inhibitors (TKIs)', and 'modern TKIs/immunotherapy'] based on the EMA approval dates of sunitinib (July 2006) and nivolumab (June 2015) in mRCC treatment. OS was considered the primary study endpoint. Kaplan–Meier analyses, log-rank tests, and uni- and multivariable Cox regression models were performed. Results: OS was significantly longer in patients of the modern TKIs/immunotherapy era (median OS not reached) as compared to the cytokine (2.4 years) and first-generation TKIs era (1.7 years, all p < 0.001). Moreover, patients of the modern TKIs/immunotherapy era demonstrated a significantly better prognosis [hazard ratio (HR): 0.41, 95% confidence interval (CI): 0.32–0.55, p < 0.001] compared to those of the cytokine era, while no statistically significant difference was observed between the cytokine and the first-generation TKIs era cohort (HR: 1.12, 95% CI: 0.89–1.41, p = 0.341). Subgroup analyses stratified by the International Metastatic RCC Database Consortium (IMDC) risk groups showed a significantly longer OS in the modern TKIs/immunotherapy era as compared to first-generation TKIs and cytokines across all IMDC risk groups. Conclusion: Significant advances in the systemic medical treatment of mRCC during the recent decade and the introduction of immunotherapy exerted a major impact on patient outcomes in terms of OS in a real-life population.